The Thyrotropin-Releasing Hormone-Degrading Ectoenzyme, a Therapeutic Target? - Charli, Jean-Louis; Rodríguez-Rodríguez, Adair; Hernández-Ortega, Karina; Cote-Vélez, Antonieta; Uribe, Rosa María; Jaimes-Hoy, Lorraine; Joseph-Bravo, Patricia (Frontiers in Pharmacology, 2020)
Thyrotropin releasing hormone (TRH: Glp-His-Pro-NH2) is a peptide mainly produced by brain neurons. In mammals, hypophysiotropic TRH neurons of the paraventricular nucleus of the hypothalamus integrate metabolic information and drive the secretion of thyrotropin from the anterior pituitary, and thus the activity of the thyroid axis. Other hypothalamic or extrahypothalamic TRH neurons have less understood functions although pharmacological studies have shown that TRH has multiple central effects, such as promoting arousal, anorexia and anxiolysis, as well as controlling gastric, cardiac and respiratory autonomic functions. Two G-protein-coupled TRH receptors (TRH-R1 and TRH-R2) transduce TRH effects in some mammals although humans lack TRH-R2. TRH effects are of short duration, in part because the peptide is hydrolyzed in blood and extracellular space by a M1 family metallopeptidase, the TRH-degrading ectopeptidase (TRH-DE), also called pyroglutamyl peptidase II. TRH-DE is enriched in various brain regions but is also expressed in peripheral tissues including the anterior pituitary and the liver, which secretes a soluble form into blood. Among the M1 metallopeptidases, TRH-DE is the only member with a very narrow specificity; its best characterized biological substrate is TRH, making it a target for the specific manipulation of TRH activity. Two other substrates of TRH-DE, Glp-Phe-Pro-NH2 and Glp-Tyr-Pro-NH2, are also present in many tissues. Analogs of TRH resistant to hydrolysis by TRH-DE have prolonged central efficiency. Structure-activity studies allowed the identification of residues critical for activity and specificity. Research with specific inhibitors has confirmed that TRH-DE controls TRH actions. TRH-DE expression by β2-tanycytes of the median eminence of the hypothalamus allows the control of TRH flux into the hypothalamus-pituitary portal vessels and may regulate serum thyrotropin secretion. In this review we describe the critical evidences that suggest that modification of TRH-DE activity in tanycytes, and/or in other brain regions, may generate beneficial consequences in some central and metabolic disorders and identify potential drawbacks and missing information needed to test these hypotheses.